2016
DOI: 10.1111/all.12946
|View full text |Cite
|
Sign up to set email alerts
|

IgG4 but no IgG1 antibody production after intralymphatic immunotherapy with recombinant MAT‐Feld1 in human

Abstract: Allergy immunotherapy (AIT) mediates protection against allergen exposure in part due to allergen-specific antibodies. While immunization typically stimulated IgG1 and IgG2, AIT is often associated with production of IgG4. Here, twenty cat dander-sensitized patients were randomized to receive three injections of intralymphatic immunotherapy (ILIT) with MAT-Feld1 adsorbed to aluminum hydroxide or just aluminum hydroxide (placebo) in a double-blind setting (ClinicalTrials.gov NCT00718679). Whereas the clinical d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 28 publications
1
25
1
Order By: Relevance
“…In NAPTs, nasal reactivity to HDM allergens was decreased after ILIT as previously described 12356. Furthermore, the serum levels of allergen-specific IgE and IgG 4 to Df and Dp were increased 4 months after ILIT, being consistent with the results of previous studies 2314. However, these levels were again decreased 1 year after ILIT.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In NAPTs, nasal reactivity to HDM allergens was decreased after ILIT as previously described 12356. Furthermore, the serum levels of allergen-specific IgE and IgG 4 to Df and Dp were increased 4 months after ILIT, being consistent with the results of previous studies 2314. However, these levels were again decreased 1 year after ILIT.…”
Section: Discussionsupporting
confidence: 90%
“…However, these levels were again decreased 1 year after ILIT. Previous studies have reported decreased allergen-specific IgE levels 3 years after ILIT1 and decreased allergen-specific IgG 4 levels 1 year after ILIT 14. Regarding dog and cat allergens, we failed to observe any significant change in the level of allergen-specific IgE or IgG 4 , due to an inadequate number of subjects.…”
Section: Discussioncontrasting
confidence: 81%
“…Also, ILIT has been successfully performed in various animal species, such as mice, rats, dogs, horses, ponies, cows, and monkeys, as reviewed previously [28]. When analysing human sera after ILIT with MAT-Fel d 1, Freiberger et al [29] recently found that the predominant immunoglobulin subclass was IgG4, whereas only marginal levels of IgG1, IgG2, and IgG3 were induced. We previously showed that this predominant IgG4 induction correlated with the allergen-specific IL-10-producing T cell response [13].…”
Section: Ilit Updatedmentioning
confidence: 99%
“…In addition, a study employing a nonclassical allergen intralymphatic immunotherapy using a modular antigen transporter Fel d 1 (MAT-Fel d 1) has found a strong increase in allergenspecific IgG4 levels and some increase in IgG2 antibody subclasses, but this procedure was not able to stimulate the production of IgG1 and IgG3 subclasses [58].…”
Section: Immunotherapy Follow-upmentioning
confidence: 99%